2000
DOI: 10.1021/bi001108u
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Collagen-Like Peptide Models of Asymmetric Acetylcholinesterase with Glycosaminoglycans:  Spectroscopic Studies of Conformational Changes and Stability

Abstract: The effect of heparin on the conformation and stability of triple-helical peptide models of the collagen tail of asymmetric acetylcholinesterase expands our understanding of heparin interactions with proteins and presents an opportunity for clarifying the nature of binding of ligands to collagen triple-helix domains. Within the collagen tail of AChE, there are two consensus sequences for heparin binding of the form BBXB, surrounded by additional basic residues. Circular dichroism studies were used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…In this context, a possible candidate is chondroitin sulfate. It has been suggested previously that chondroitin sulfate proteoglycans interact with asymmetric AChE (34,35), and we have observed previously a direct interaction between chondroitin sulfate and the peptides modeling the N-and C-terminal HBDs, whose characteristics also differed between the two sites (14).…”
Section: Heparin-binding Capacity Of Colq Resides Exclusively In the supporting
confidence: 57%
See 2 more Smart Citations
“…In this context, a possible candidate is chondroitin sulfate. It has been suggested previously that chondroitin sulfate proteoglycans interact with asymmetric AChE (34,35), and we have observed previously a direct interaction between chondroitin sulfate and the peptides modeling the N-and C-terminal HBDs, whose characteristics also differed between the two sites (14).…”
Section: Heparin-binding Capacity Of Colq Resides Exclusively In the supporting
confidence: 57%
“…The effect of the distant environment may also explain the fact that the wild type enzyme with both HBDs exhibits a greater affinity for heparin than each HBD independently. We have previously shown that triple-helical content and stability increase upon heparin binding to a HBD (14). Thus, such a perturbation induced by heparin binding to one HBD could propagate along the triple helix, altering the conformation of the other HBD and increasing its affinity for heparin.…”
Section: Heparin-binding Capacity Of Colq Resides Exclusively In the mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the homotrimer has a triple-helical conformation, whereas HepV does not, as demonstrated by circular dichroism, and that might contribute to their different requirements for sulfate group binding. It has been previously reported for the heparin binding domains of the acetylcholinesterase collagen tail that the addition of increased amounts of heparin can increase the triple helix content and the thermal stability of triple-helical peptide models (40,41). However, the addition of heparin and heparan sulfate at different concentrations failed to induce significant structural change in HepV even during an overnight incubation.…”
Section: Inhibitionmentioning
confidence: 93%
“…A histidine in the catalytic subunit of ACHE accelerates its rate of cationic ligand binding [103]. The ACHE collagen tail has 2 consensus sequences that bind heparin and are surrounded by additional basic residues which enhance the heparinbinding affinity [104]. Anionic heparin inhibition of cation effects, of basic amino acid residues (histidine, arginine, lysine) and of HSPG, strongly suggests that heparin would ameliorate the harmful effects of ACHE.…”
Section: Acetylcholine Esterasementioning
confidence: 99%